Statens livsnødvendige cirkulation: Handel som livsvigtigt princip for den moderne stat - Jessen, Mathias Hein (K&K - Kultur og Klasse, 2017)
The article analyzes the role of trade in the constitution of the modern state in 17th century England. The article focuses on the metaphor of the body politic and especially the ideas on circulation from William Harvey and how these can be used to analyze Thomas Hobbes’ ideas on trade and circulation in Leviathan and the economic thought of William Petty. Harvey’s thoughts on circulation were revolutionary and highly influential on the political and economic thoughts of the time. Even though Hobbes is mainly focused on law and sovereignty, he still characterizes circulation and trade as a vital motion, not subject to the will of the sovereign. Combined with his notion that the sovereign is the holder of an office, who must administer the wellbeing of the state, this opens up for the analysis that what the sovereign is administering is in reality the necessary motions of trade and the economy in general. This is also seen in one of the most prominent of the mercantilist economic thinkers of the age, William Petty, who in his economic thinking contributed to the constitution of the economy as a given field with a given logic which the ruler could not fundamentally change, but had to understand and act in accordance with in order to govern well.